Cardiac vagal modulation predicts decision-making in sacrificial and everyday moral dilemmas - Rebecca Prell; Martina Anna Maggioni; Katrin Starcke (Scientific Reports)
Abstract Cardiac vagal modulation indicates the self-regulatory activity of the autonomic nervous system and can thus be used to assess an individual’s ability to integrate physiological, cognitive, and emotional responses in the decision-making process. In this paper, cardiac vagal modulation, quantified by heart rate variability (HRV), was used to predict decision-making in two types of moral dilemmas: First, sacrificial dilemmas which create a moral conflict between utilitarian (acting to maximise aggregate well-being by sacrifice) and deontological (rejecting the sacrifice) alternatives; second, everyday dilemmas which create a conflict between altruistic (acting non-selfish) and egoistic (acting self-centered) alternatives. HRV was analysed in 112 healthy participants before, during, and after decision-making, allowing to assess not only self-regulatory ability (resting HRV) but also self-regulatory capacities (HRV during and after decision-making). HRV predicted concrete decisions, but effects were only found in women. In sacrificial dilemmas, deontological women showed a stronger vagal withdrawal but also a faster cardiac vagal recovery compared to high utilitarian women. In everyday moral dilemmas, altruism was associated with reduced vagal outflow and increased sympathetic activity. Findings suggest differences in the acquisition of self-regulatory capacities between decision-makers in both types of moral dilemmas, which can be measured by HRV.